Religion and the gender vote gap: women's changed political preferences from the 1970s to 2010 - Manow, Philip,Emmenegger, Patrick (online, 2012)
Abstract:
urn:nbn:de:0168-ssoar-366974
Keywords: (stw)1970-2010; (stw)Wahlverhalten; (stw)Geschlecht; (stw)Religion; (stw)EU-Staaten; (thesoz)Wahlverhalten; (thesoz)Frau; (thesoz)historische Entwicklung; (thesoz)geschlechtsspezifische Faktoren; (thesoz)Religion; (thesoz)Einkommensunterschied; (thesoz)Bildungsniveau; (thesoz)politische Einstellung; Arbeitspapier; Online-Publikation; Graue Literatur; Wahlverhalten; Gender; Religion; :z Geschichte 1970-2010